The 'Little Palaces' of St James's: Ladies, Lords, and Political Association under the later Stuarts. (10th February 2020) - Harris, Frances
Abstract: Clubs, coffee houses, and taverns, the most widely studied sites of political gathering in later Stuart London, largely excluded women. This essay argues that places of 'intermixed conversation' which existed alongside them should also be taken into account, and considers several examples of regular, semi‐private assemblies, chiefly hosted by elite women (including duchesse de Mazarin, Lady Pulteney, and Barbara Villiers, Lady Fitzhardinge) and frequented by both sexes for the overt purpose of card playing, which were also significant places of political association at this period.